Development of an integrated control system for rescue boat - Muhammad Razif, Muhammad Rusydi; Azhar, Nurul Nabilah; Sadun, Amirul Syafiq; Mohd Nordin, Ili Najaa Aimi; Akmar Zulkifli, Nor Saradatul (2020)
During flood season, fire department or rescuing team are facing the situation which is lack of man power. To overcome this problem, an integrated rescuing boat control system has been proposed. The developed rescuing boat controller is convenience and easy to handle. It has been built with an integrated system which could be handled manually or automatically. The controller is developed using microcontroller Arduino. For an autonomous mode, some sensors has been introduced to sense the obstacles and giving the instruction to the Arduino to changed the direction of the boat. For manual control, rescuing boat could be controlled by Blynk application through smart phone. By introcuding an integrated rescuing boat control system, the victim can save their own from dangerous and reduce dramatically the number of death or injuries due to the flood.